2013
DOI: 10.1016/j.pmrj.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Connections Between Traumatic Brain Injury Caregiver Mental Health and Family Dynamics in Mexico City, Mexico

Abstract: TBI caregiver interventions in Latino populations would likely benefit from including programming or techniques to improve family dynamics, especially family cohesion, given the strong potentially reciprocal influence of these dynamics on caregiver mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 50 publications
2
18
0
5
Order By: Relevance
“…They show that burden is usually associated with lower socio-economic status and with poor outcomes for the dependent older person (Chen et al, 2016). Some studies identify associations between positive family dynamics and family cohesion (defined in general terms) and reduced carer burden (Elnasseh et al, 2016;Perrin et al, 2013). These findings are closely in line with those of similar studies in high income countries.…”
Section: Introductionsupporting
confidence: 68%
“…They show that burden is usually associated with lower socio-economic status and with poor outcomes for the dependent older person (Chen et al, 2016). Some studies identify associations between positive family dynamics and family cohesion (defined in general terms) and reduced carer burden (Elnasseh et al, 2016;Perrin et al, 2013). These findings are closely in line with those of similar studies in high income countries.…”
Section: Introductionsupporting
confidence: 68%
“…Studies carried out in other cultures 27,28 in the context of health have revealed more difficulties related to family cohesion, flexibility and communication. This strengthens the idea that having a child with CP of helplessness, insecurity and frustration in the face of the child's functional and developmental constraints and losses.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto à comunicação e satisfação familiares, um estudo realizado no México com cuidadores de pessoas que sofreram traumatismo cranioencefálico (PERRIN et al, 2013) encontrou uma média um pouco mais alta em comunicação (38,2 comparado com 36,6 para o presente estudo) e mais baixa para satisfação com a família (27,9 para 30,5). Ainda que os resultados quanto à comunicação familiar sejam satisfatórios nos dois casos (36,6 e 38,2 em uma escala que poderia variar de 10 a 50) é interessante observar maior satisfação dos cuidadores brasileiros com suas famílias.…”
Section: Discussionunclassified
“…Ainda, o estudo de Perrin et al (2013) encontrou uma associação entre sobrecarga do cuidador e dinâmica familiar, sendo que a presença de algum nível clínico de sobrecarga apresentou correlação inversa com as variáveis ligadas ao bom funcionamento familiar.…”
Section: Discussionunclassified
See 1 more Smart Citation